KONSEKUENSI HUKUM OBJEK JAMINAN FIDUSIA YANG BELUM DIDAFTARKAN BAGI LEMBAGA PEMBIAYAAN SEBAGAI KREDITOR (Studi Kasus: Putusan Mahkamah Agung Republik Indonesia No. 140 K/Pid/2012) - , Deidira Deviany Putri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study was to determine funding position as fiduciary creditor if the debtor has not filed while in default and to determine the legal consequences received financial institutions as creditors when carrying out the execution of fiduciary objects that have not been registered. The preparation of this thesis is based on field research to obtain primary data and literature research to obtain secondary data, with each technique through interviews and document study. All data were then analyzhed with qualitative methods. The results of this study are position of financial institutions as creditors object fiduciary if not registered while the debtor is in default creditors have no rights or preferential rights that preceded the creditor does not have the right to execute because it has not had a fiduciary certificates and accepted legal consequences as a creditor financial institutions carry out the execution of an object that has not been registered fiduciary creditor is deemed to act against the law for execution as a sign that the object of the guarantee has been registered to the registration office fiduciary.